THORACIC SURGERY Anti-angiogenic agents in the treatment of non-small cell lung cancer - Szyszka-Barth, Katarzyna; Ramlau, Katarzyna; Stencel, Dariusz; Ramlau, Rodryg (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Lung cancer is the most common malignant neoplasm diagnosed worldwide. In Poland, in 2011, lung cancer was diagnosed in 14,522 men and 6,283 women. Morbidity and mortality are nearly equal, and lung cancer is still the most common cause of cancer-related death among men as well as among women. Approximately 80% of lung cancer cases are non-small-cell lung cancer. The most commonly applied chemotherapy regimens do not produce satisfactory effects. Oncological research is now focused on molecular targeted therapies; immunotherapy is also under evaluation. The formation of abnormal blood vessels has an enormous impact on the development and progression of a tumor. Bevacizumab is a monoclonal antibody which binds VEGF (vascular endothelial growth factor). A different group of drugs is constituted by small-molecule antiangiogenic tyrosine kinase inhibitors. These agents represent a different profile of side effects in comparison to chemotherapy. The mode of action, differing from cytotoxic drugs, requires renewed analysis as well as standardization of radiological response assessment criteria.